Analysis of self-hisbah factors on moral appreciation among Muslim secondary school students in Malaysia : Fuzzy Delphi method application - Ros Arniza Zakaria,; Mohd Isa Hamzah,; Khadijah Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The issue of moral deterioration among secondary school students still transpires due to the lack of moral appreciation among them. It is caused by the practice of self-hisbah, which is not attended in an istiqamah (steadfast) manner. The factor of self-hisbah potentially impacts the appreciation of the morals of Muslim students. This research aimed to analyse the self-hisbah factor by examining the expert consensus on the elements found in the self-hisbah factor. The researchers chose elements of the hisbah of heart and soul, hisbah of lust, and hisbah of behaviour. This study employed a quantitative approach that surveyed the views and evaluations of 14 experts selected by purposive sampling. These experts evaluated three (3) elements and twenty (20) items included in the Model of Moral Appreciation of Muslim secondary students. The researchers analysed the obtained data using the Fuzzy Delphi method. The analysis considered the triangular Fuzzy Numbers and the ranking of elements obtained through Defuzzification. The study data confirmed that the response and expert consensus on all elements were good. In essence, expert consensus exceeded 75%, and almost all threshold values ’d’ met consensus conditions. This analysis contributes to the theory of hisbah. Internal hisbah signifies the power to act emerges from oneself due to a process of self-evaluation known as hisbah. The practice of self-hisbah delivers a person who is always disciplined and strives to do good and refrain from doing evil in his daily life as a student. This theory is pertinent to be included in the Model of Moral Appreciation of Muslim Students’ secondary schools in Malaysia. A quantitative study is germane to be conducted on secondary school students throughout Malaysia to examine the usability of the model.